2000
DOI: 10.1123/jab.16.4.356
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Importance of Wrist Torque in Driving the Golfball: A Simulation Study

Abstract: The purpose of this study was to examine whether, in theory, the clubhead speed at impact could be increased by an optimally timed wrist torque, without jeopardizing the desired club position at impact. A 2-D, three-segment model comprising torso, left arm, and golfclub was used to model the downward phase of the golf swing. Torque generators that adhered to the activation and force-velocity properties of muscle were inserted at the proximal end of each segment. Separate simulations were performed, with the wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 14 publications
9
71
0
3
Order By: Relevance
“…An established method of measuring golf driving performance has been to determine the magnitude of club head speed (8,10,14,19,20),which is dependent on many factors including the amount and direction of ground reaction force produced (1), and the use of the kinetic chain sequencing (34).…”
Section: Introductionmentioning
confidence: 99%
“…An established method of measuring golf driving performance has been to determine the magnitude of club head speed (8,10,14,19,20),which is dependent on many factors including the amount and direction of ground reaction force produced (1), and the use of the kinetic chain sequencing (34).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that reducing the radius path of the hands during the downswing (Nesbit, 2005a), increasing wrist torque (Nesbit, 2005a;Sprigings & Mackenzie, 2002a;Sprigings & Neal, 2000), increasing wrist range of motion (Nesbit, 2005a) and delaying relative wrist motion to late in the downswing (Nesbit, 2005a) all increase ball displacement or clubhead velocity.…”
Section: What Predicts Golf Performance -Biomechanical Variables Of Imentioning
confidence: 99%
“…Simulation studies utilsing 2-D, three segment models with joint torque generators (Sprigings & Mackenzie, 2002b;Sprigings & Neal, 2000) or 3-D, full body models (Nesbit, 2005a) have demonstrated the important role of the wrist in the golf swing.…”
Section: What Predicts Golf Performance -Biomechanical Variables Of Imentioning
confidence: 99%
See 2 more Smart Citations